The effect of aging on the brain network for exception word reading. (November 2016) - Provost, Jean-Sebastien; Brambati, Simona M.; Chapleau, Marianne; Wilson, Maximiliano A.
Abstract: Cognitive and computational models of reading aloud agree on the existence of two procedures for reading. Pseudowords (e.g., atendier) are correctly read through subword processes only while exception words (e.g., pint) are only correctly read via whole-words processes. Regular words can be correctly read by means of either way. Previous behavioral studies showed that older adults relied more on whole-word processing for reading. The aim of the present fMRI study was to verify whether this larger whole-word reliance for reading in older adults was reflected by changes in the pattern of brain activation. Both young and elderly participants read aloud pseudowords, exception and regular words in the scanner. Behavioral results reproduced those of previous studies showing that older adults made significantly less errors when reading exception words. Neuroimaging results showed significant activation of the left anterior temporal lobe (ATL), a key region implicated in whole-word reading for exception word reading in both young and elderly participants. Critically, ATL activation was also found for regular word reading in the elderly. No differences were observed in the pattern of activation between regular and pseudowords in the young. In conclusion, these results extend evidence on the critical role of the left ATL for exception word reading to elderly participants. Additionally, our study shows for the first time from a developmental point of view that the behavioral changes found in reading during normal aging also have a brain counterpart in the reading network changes that sustain exception and regular word reading in the elderly.